ナンキョクカイ デノ チキュウ カガク テキ ケンキュウ ノ ショウライ ケイカク ニ カンスル ケンキュウ ショウシュウカイ ホウコク - 野木, 義史; ノギ, ヨシフミ; Nogi, Yoshifumi (2000)
P(論文) 2000年2月17日に「南極海での地球科学的研究の将来計画」に関する研究小集会を行った。本研究小集会は, 南極海での固体地球科学の分野での現在の様々な問題点を明確にし, 国内外の観測船の動向を把握する事により, 将来の南極海での固体地球科学的調査計画の具体化を目的とした。本研究小集会を通じて, 南極海での固体地球科学的観測の重要性を再認識し, 今後, 本研究小集会参加者を中心に観測計画を現実化に向けてより具体化していくこととなった。 A workshop on "Future research plans for solid Earth sciences in the Antarctic Ocean" was held on February 17,2000. The main object of the workshop was to make concrete research plans for solid Earth sciences in the Antarctic Ocean by clarifying various solid Earth scientific problems in the Antarctic Ocean and determining the present research programs of Japanese and foreign research vessels. The importance of the solid Earth scientific observation in the Antarctic Ocean was emphasized throughout the workshop. Workshop participants will draw up feasible projects in the near future. departmental bulletin paper